Thrombolysis for acute ischemic stroke: results of the Canadian Alteplase for Stroke Effectiveness Study. - Hill, MD; Buchan, A (2005)
BACKGROUND: Thrombolysis for acute ischemic stroke has remained controversial. The Canadian Alteplase for Stroke Effectiveness Study, a national prospective cohort study, was conducted to assess the effectiveness of alteplase therapy for ischemic stroke in actual practice. METHODS: The study was mandated by the federal government as a condition of licensure of alteplase for the treatment of stroke in Canada. A registry was established to collect data over 2.5 years for stroke patients receiving such treatment from Feb. 17, 1999, through June 30, 2001. All centres capable of administering thrombolysis therapy according to Canadian guidelines were eligible to submit patient data to the registry. Data collection was prospective, and follow-up was completed at 90 days after stroke. Copies of head CT scans obtained at baseline and at 24-48 hours after the start of treatment were submitted to a central panel for review. RESULTS: A total of 1135 patients were enrolled at 60 centres in all major hospitals across Canada. The registry collected data for an estimated 84% of all treated ischemic stroke patients in the country. An excellent clinical outcome was observed in 37% of the patients. Symptomatic intracranial hemorrhage occurred in only 4.6% of the patients (95% confidence interval [CI] 3.4%-6.0%); however, 75% of these patients died in hospital. An additional 1.3% (95% CI 0.7%-2.2%) of patients had hemiorolingual angioedema. CONCLUSIONS: The outcomes of stroke patients undergoing thrombolysis in Canada are commensurate with the results of clinical trials. The rate of symptomatic intracranial hemorrhage was low. Stroke thrombolysis is a safe and effective therapy in actual practice.